(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2009)
The article presents different thematic (lexical-semantic) fields and graups of lexical (material and stylistic) archaisms, represented by creative legacy of J. Nechuy-Levitsky, which first of all reflect historical and cultural heritage of Ukrainian people. The studing of lexical archaisms on the material of fiction legacy of writer is considered as that, which assists with enrichment of pupils lexicon, better understanding of syllabus compositions.